Capturing the perspectives of women with coronary artery disease regarding interval training or continuous exercise in cardiac rehabilitation. Issue 1 (11th January 2022) - Lee, Leanna S.; Banks, Laura; Oh, Paul I.; Brooks, Dina; Colella, Tracey J. F.
Abstract: Background: Motivators and barriers to exercise participation in women with coronary artery disease remain poorly understood. With evidence suggesting that women with coronary artery disease are less likely to adhere to exercise during cardiac rehabilitation and are more likely to drop out, it is important to understand these factors in order to optimize cardiac rehabilitation programs for women. Methods: We contribute to the discussion by presenting findings from a qualitative study using two focus groups with nine women with coronary artery disease sharing their experiences with attending cardiac rehabilitation and exercising in this setting, in addition to their perceived motivators and barriers to performing aerobic interval training. Focus group transcripts were analysed using a deductive thematic approach with Bandura's Social Cognitive Theory as the guiding conceptual framework. Results: Four themes were identified regarding the attitudes and experiences of attending and exercising at cardiac rehabilitation, while five themes capturing the motivators and barriers for these women to perform aerobic interval training were identified for the first time. These novel themes encompassed the daunting nature of it, the physical discomfort associated with it, and conversely, the potential sense of enjoyment and accomplishment that it could bring. Conclusion: This study demonstrates the complexity of implementation of aerobic interval training into clinical practice, and suggests that further research is warranted to explore this domain. IMPLICATIONS FOR REHABILITATION: Despite challenges in feasibility of conducting a randomised controlled trial in female patients with coronary artery disease examining the effects of aerobic interval training versus moderate-intensity continuous exercise on aerobic exercise capacity, there was a significant per protocol treatment effect of 0.95 ml·kg −1 ·min −1 in favour of aerobic interval training. The cardiac rehabilitation environment provides key facilitators and perceived benefits for exercising and attending cardiac rehabilitation for women, and thus emphasises the need for improving referral and enrolment processes specifically for women into cardiac rehabilitation programs. Aerobic interval training may elicit feelings of fear and physical discomfort, or may be precluded by comorbid conditions, therefore, judicious consideration must be taken in examining the suitability of implementation into clinical practice for each female patient.